Epidemiological features of rosacea in Changsha, China: A population‐based, cross‐sectional study. Issue 5 (24th March 2020) - Li, Jinglin; Wang, Ben; Deng, Yuxuan; Shi, Wei; Jian, Dan; Liu, Fangfen; Huang, Yingxue; Tang, Yan; Zhao, Zhixiang; Huang, Xin; Li, Ji; Xie, Hongfu
Abstract: Rosacea is a common chronic skin disorder of unknown etiology. While population prevalence rates range 0.2–22% in Europe and North America, prevalence in China is currently undetermined. We conducted a large population‐based case–control study to determine the present epidemiological status of rosacea in China, involving 10 095 participants aged 0–100 years (mean age, 35.5 ± 19.1; 50.5% female). A census of rosacea among 15 communities in Changsha in south central China was conducted with skin examination by board‐certified dermatologists. Rosacea was observed in 3.48% (95% confidence interval, 3.13–3.85%) of the study population. Subtype distribution was erythematotelangiectatic in 47.6%, papulopustular in 35.0% and phymatous in 17.4%. Family history was noted in 37.8% and ocular symptoms in 31.3%. Associations with rosacea were observed for melasma, hypertension, hyperthyroidism and breast cancer in females ( P  < 0.05), and also for hyperthyroidism and peptic ulcers in males ( P  < 0.05). Our results provide baseline information about epidemiological aspects of rosacea in China.